2021
DOI: 10.3389/fnins.2021.679092
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Diseases and Parkinson Disease: A Population-Based Study

Abstract: IntroductionPatients with Parkinson disease (PD) tend to have ophthalmic symptoms. Retinal diseases are associated with central nervous system diseases, especially neurodegenerative diseases. Here, we investigated the association of retinal diseases with PD, especially the temporal relationship before and after PD diagnosis.MethodsData were obtained from the National Health Insurance Research Database of Taiwan. In total, 21,845 patients with newly diagnosed PD were matched with four controls each on the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…On the one hand, it is well established that depressive individuals suffer from deficits of the dopaminergic system (for reviews, Belujon & Grace, 2017; Delva & Stanwood, 2021; Dunlop & Nemeroff, 2007). On the other hand, dopamine acts within the retina (Chen et al, 2021; Ghilardi et al, 1989; Weil et al, 2016), which is regarded as the first processing stage of the visual system (for a recent review, Pokorny & Smith, 2020). Previous studies have shown that the abnormality in contrast sensitivity is associated with reduced dopamine activity in the retina (Bodis‐Wollner et al, 1987; Langheinrich et al, 2000; Polo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, it is well established that depressive individuals suffer from deficits of the dopaminergic system (for reviews, Belujon & Grace, 2017; Delva & Stanwood, 2021; Dunlop & Nemeroff, 2007). On the other hand, dopamine acts within the retina (Chen et al, 2021; Ghilardi et al, 1989; Weil et al, 2016), which is regarded as the first processing stage of the visual system (for a recent review, Pokorny & Smith, 2020). Previous studies have shown that the abnormality in contrast sensitivity is associated with reduced dopamine activity in the retina (Bodis‐Wollner et al, 1987; Langheinrich et al, 2000; Polo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the nervous system is frequently impacted in syndromic retinal disorders, including Alzheimer's disease patients and animal models [19,20]. In addition, alterations in the structure of the retina and choroid, as well as in its microvasculature, occur as part of nonmotor symptoms observed in Parkinson's Disease [21,22]. In Batten disease, the classic juvenile form of human neuronal ceroid lipofuscinosis, ocular symptoms manifest before neurologic symptoms [23], while in CLN8 neuronal ceroid lipofuscinosis, disease progression (onset of myoclonus and cognitive impairment) is rapid, and visual loss is often noted within two years of diagnosis [24].…”
Section: Introductionmentioning
confidence: 99%